Flow and Noise Characteristics of Centrifugal Fan under Different Stall Conditions. (22nd May 2014) - Zhang, Lei; Liang, Shoufang; Hu, Chenxing
Abstract : An implicit, time-accurate 3D Reynolds-averaged Navier-Stokes (RANS) solver is used to simulate the rotating stall phenomenon in a centrifugal fan. The goal of the present work is to shed light on the flow field and particularly the aerodynamic noise at different stall conditions. Aerodynamic characteristics, frequency domain characteristics, and the contours of sound power level under two different stall conditions are discussed in this paper. The results show that, with the decrease of valve opening, the amplitude of full pressure and flow fluctuations tends to be larger and the stall frequency remains the same. The flow field analysis indicates that the area occupied by stall cells expands with the decrease of flow rate. The noise calculation based on the simulation underlines the role of vortex noise after the occurrence of rotating stall, showing that the high noise area rotates along with the stall cell in the circumferential direction.